Implementation of Nurse-Led, Goal-Directed Lung Physiotherapy for Older Patients With Sepsis and Pneumonia in the ICU - Sun, Jianhua; Cui, Na; Han, Wen; Li, Qi; Wang, Hao; Li, Zunzhu; Cheng, Wei; Luo, Hongbo; Zhao, Mingxi (Frontiers in Medicine, 2021)
Objectives: This study aimed to investigate the effect of nurse-led, goal-directed lung physiotherapy (GDLPT) on the prognosis of older patients with sepsis caused by pneumonia in the intensive care unit. Methods: We conducted a prospective, two-phase (before-and-after) study over 3 years called the GDLPT study. All patients received standard lung therapy for sepsis caused by pneumonia and patients in phase 2 also received GDLPT. In this study, 253 older patients (age ≥65 years) with sepsis and pneumonia were retrospectively analyzed. The main outcome was 28-day mortality. Results: Among 742 patients with sepsis, 253 older patients with pneumonia were divided into the control group and the treatment group. Patients in the treatment group had a significantly shorter duration of mechanical ventilation (5 [4, 6] vs 5 [4, 8] days; P=0.045), and a lower risk of intensive care unit (ICU) mortality (14.5% [24/166] vs 28.7% [25/87]; P=0.008) and 28-day mortality (15.1% [25/166] vs 31% [27/87]; P=0.005) compared with those in the control group. GDLPT was an independent risk factor for 28-day mortality (odds ratio [OR], 0.379; 95% confidence interval [CI], 0.187–0.766; P=0.007). Conclusions: Nurse-led GDLPT shortens the duration of mechanical ventilation, decreases ICU and 28-day mortality, and improves the prognosis of older patients with sepsis and pneumonia in the ICU.